Ferroelectric Nanogap‐Based Steep‐Slope Ambipolar Transistor. Issue 48 (30th September 2022) - Guan, Yaodong; Guo, Zhe; You, Long
Abstract: The subthreshold swing (SS) of metal–oxide‐semiconductor field‐effect transistors is limited to 60 mV dec −1 at room temperature by the Boltzmann tyranny, which restricts the scaling of the supply voltage. A nanogap‐based transistor employs a switchable nanoscale air gap as the channel, offering a steep‐slope switching process. Meanwhile, nanogaps featuring even sub‐3 nm can efficiently block the current flow, exhibiting the potential for tackling the short‐channel effect. Here, an electrically switchable ferroelectric nanogap to construct steep‐slope transistors, is exploited. An average SS of 15.9 mV dec −1 across 5 orders and a minimum SS of 13.23 mV dec −1 are obtained in the high current density range. The transistor exhibits excellent performance with near‐zero off‐state leakage current and a maximum on‐state current of 202 µA µm −1 at V DS = 0.5 V. In addition, the transistor can turn off with either a positive or negative increase in the gate voltage, exhibiting ambipolar characteristics. Abstract : A steep‐slope transistor based on switchable ferroelectric nanogap is proposed with excellent performance such as low subthreshold swing as well as high steep‐slope current densities. Moreover, the transistor shows ambipolar characteristics. This transistor has potential as a type of emerging steep‐slope device in the era of hyper Moore's law.